THE ERGOGENIC POTENTIAL OF AN OAT-BASED ENERGY BAR: A COMPREHENSIVE NUTRITIONAL EVALUATION - S. ARCHANA,; V. AKHILA, (The Journal of Research ANGRAU, 2024)
The study was conducted during the year 2022 and the objective was to develop a minimally processed energy bar using peanuts, oats, whey, dates, and pumpkin seeds. The ideal composition of the energy bar was determined as a combination of 60% oats and 40% peanuts, based on the sensory analysis. The energy bar exhibited a moisture content of approximately 10%, ash content of 1.55%, crude fat content of 16.42%, crude fibre content of 3.73%, and crude protein content of 20.83%. The energy value was calculated as 213.13 kcal per serving. The hardness value of the energy bar was found to be 150 ± 0.870 N. The nutritional analysis of this minimally processed energy bar suggested it is a convenient and functional ergogenic aid for health-conscious people, particularly athletes, and active individuals.